Diseño y fabricación de un dispositivo que permite la inserción certera en el espacio peritoneal del catéter usado en la derivación ventrículo-peritoneal: TechIBIO (2020)
During the ventricular-peritoneal shunt, a surgical procedure that aims to treat hydrocephalus, the location of a catheter from the cerebral ventricle to the peritoneal cavity is required, where cerebrospinal fluid is naturally drained or absorbed. However, to get through an incision to the peritoneal space, extensive skills are required, which general surgeons acquire over time. However, according to the testimonies of some neurosurgeons linked to the Colombian Association of Neurosurgery, on many occasions, in order to reduce costs, the hospitals assign this task to them despite not being their specialty and therefore, they perform this procedure, liable to the possibility of making mistakes such as perforation of the peritoneum. After a long prototyping process, Derivatech, a device that facilitates neurosurgeons to correctly locate the drainage tube of cerebrospinal fluid in the peritoneal space, during the ventricular-peritoneal shunt, was reached. Its design was accomplished through Autodesk Inventor and its manufacture, using 3D printing. The validation process in clinical trials presented promising results that show the potential of this device to solve the problem successfully.--Taken from the Degree Document Format.